The Key of Customer’s Satisfaction and Loyalty: E-Service Quality, Price, and Trust - Fiqhi Fachrizal; Maria Apsari Sugiat; Irni Yunita (Journal of Economics and Business UBS, 2023)
Some companies do not reach sustainability because of the lack of innovation in products, services, and marketing, With the aim of growing the customer count as well as to maintain existing customers. Currently, competition in the telecommunications industry is very tight due to the increasing number of internet providers, such as Indihome, Biznet, Iconnet, and other official and unofficial local ISPs. Internet provider companies must be able to enhance the quality of services and products that are capable of reaching various economic levels, including upper, middle, and lower levels, as the demand for internet continues to grow, even in rural areas. This research endeavors to analyze e-service quality, web design, price, and trust affect the level of satisfaction and loyalty of Indihome customers. The quantitative research design is being utilized. The type of research used is descriptive. New Indihome users in the Datel Situbondo area were the focus of the study who started subscribing since the first semester period of 2022, which totalled 1059 people. Researchers used purposive sampling technique to collect sample of 290 respondents. This research covers Situbondo Representative Office area which is divided into 4 regions, consisting of Situbondo, Mlandingan, Besuki, and Asembagus. Drawing from the research results, e-service quality, price, and trust each have a positively effect on customer satisfaction and customer loyalty. Customer satisfaction is related to customer loyalty. As customer satisfaction rises, so does customer loyalty.